The Properties and Utility of Less Evaluative Personality Scales: Reduction of Social Desirability; Increase of Construct and Discriminant Validity - Bäckström, Martin; Björklund, Fredrik (Frontiers in Psychology, 2020)
Evaluative neutralization implies rephrasing items such that it is less clear to the respondent what would be a desirable response in the given population. The current research introduces evaluatively neutralized scales measuring the FFM model and compares them with standard counterparts. Study 1 reveals that evaluatively neutralized scales are less influenced by social desirability. Study 2 estimates higher-order factor models for neutralized vs. standard five-factor scales. In contrast to standard inventories, there was little support for higher-order factors for neutralized scales. Study 3 demonstrates the convergent and discriminant validity for the neutralized scales, e.g. by less inflated correlations to external measures. It is argued that evaluatively neutralized inventories help researchers come to grips with social desirability in personality measurement, and are particularly useful when the factor structure is central to the research question and there is a focus on discriminant validity.